Faktor-faktor penyumbang kepada pengayaan kerja -keluarga dalam kalangan pekerja sektor awam - Khadijah, Binti Ali Othman (Universiti Malaysia Sarawak, UNIMAS, 2011)
This study aims to identify the factors that contribute to work-family enrichment. The employee's perception was investigated from related aspects such as work-family enrichment, familY-lvork enrichment, family support, job involvement, colleagues support. job characteristic, and supervisor support. This research design is quantitative study using survey questionnaire designed by the past researchers. A convenience sampling method was used to select the t; employees from different divisions & functional areas in Pejabat Kesihatan Miri and Institut i; ",1 " Latihan Perindustrian Miri. Data processing was analyzed using Statistical Package ','1 ' for the ".~ '~ Social Science (SPSS 17.0) software to find the frequency, Pearson Correlation Analysis, and Multiple Regression. The findings shows that there is a significant relationship between family support, colleagues support, job characteristic, and supervisor support towards work-family enrichment. However, the findings show there is no significant relationship between job involvements towards work-family enrichment. Beside that, Multiple Regression was used to identify dominant factor that influence work-family enrichment. Family Support is identify as the I. dominant factor. From the findings, the organization should establish work-life balance policies and promotes organizational cultures that are more sensitive to employee work and family " , .' needs.